2023
DOI: 10.1002/advs.202207490
|View full text |Cite
|
Sign up to set email alerts
|

Nanomedicines Reprogram Synovial Macrophages by Scavenging Nitric Oxide and Silencing CA9 in Progressive Osteoarthritis

Abstract: Osteoarthritis (OA) is a progressive joint disease characterized by inflammation and cartilage destruction, and its progression is closely related to imbalances in the M1/M2 synovial macrophages. A two‐pronged strategy for the regulation of intracellular/extracellular nitric oxide (NO) and hydrogen protons for reprogramming M1/M2 synovial macrophages is proposed. The combination of carbonic anhydrase IX (CA9) siRNA and NO scavenger in “two‐in‐one” nanocarriers (NAHA‐CaP/siRNA nanoparticles) is developed for pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 66 publications
(29 reference statements)
1
20
0
Order By: Relevance
“…Several reports suggest that elevated NO levels are associated with the production of pro-inflammatory cytokines, such as TNF-α, IL-6, and IL-1β. 55,56 These cytokine levels were quantified in LPS-stimulated macrophages following treatment with the samples (Fig. 4E and F).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports suggest that elevated NO levels are associated with the production of pro-inflammatory cytokines, such as TNF-α, IL-6, and IL-1β. 55,56 These cytokine levels were quantified in LPS-stimulated macrophages following treatment with the samples (Fig. 4E and F).…”
Section: Resultsmentioning
confidence: 99%
“…The cytotoxicity of NSc and HA–NSc conjugate was evaluated using MTT assay. For this purpose, RAW 264.7 cell, a murine macrophage cell line known for their ability to produce high levels of NO and pro-inflammatory cytokines upon lipopolysaccharide (LPS) stimulation, 55,56 was utilized. As depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Dex also showed an inhibitory effect on CA9 mRNA expression, which was consistent with the previous report. 11 This effect may be attributed to its inhibition of inflammation regulatory factor HIF-1α. 27 The mRNA levels of IL-12 (the marker of M1 macrophage) and IL-10 (the marker of M2 macrophage) were detected to characterize the effects of AHK-CaP/siCA9 NPs on macrophage repolarization.…”
Section: Resultsmentioning
confidence: 99%
“…10 Our previous study had identified that the downregulation of overexpressed carbonic anhydrase IX (CA9) on synovial macrophages in OA, a transmembrane protein closely related to intracellular and extracellular acid microenvironment, could achieve great inflammatory regulation effect. 11 The CA9 targeting siRNA (siCA9)-loaded nanoparticles (NPs) successfully reversed the inflammatory microenvironment through reprogramming macrophages from the M1 to M2 phenotype. Therefore, the regulation of inflammatory microenvironment is essential for improving MSCs efficiency in OA therapy.…”
mentioning
confidence: 99%
“…The classical pharmacological approach to the treatment of inflammatory conditions is based on the use of medicines able to reduce the synthesis of the inflammatory mediators involved. However, recent studies have focused on attempting to modulate the profile of pivotal inflammatory cells, such as macrophages and neutrophils, involved in triggering and maintaining the phenomenon [5–7].…”
Section: Introductionmentioning
confidence: 99%